An Innovation of Geo-Logistics toward Sustainable Strategies for Small and Medium-Sized Ports in Thailand - Netirith, Narthsirinth; Poma, Worawut; Chotechuang, Naruphun; Mudunkotuwa, Rashika Sanjeewani; Aden, Waiss Ali; Sirichokpokin, Punarut (Sustainable Marine Structures, 2025)
This study investigates the integration of geo-logistics as a strategic framework for enhancing sustainability within Small and Medium-sized Ports (SMPs) in Thailand, focusing on improving environmental ,innovation and economic performance. The geo-logistics framework in this study considers the spatial  aspects of logistics activities around the port areas to achieve sustainability goals. This research employs a mixed-methods approach  statistical analysis  (ANOVA), combined with semi-structured interviews and an intensive literature review to assess both internal and external management criteria across three key regional ports—Songkhla, Map Ta Phut, and Ranong. Findings reveal significant variations of internal factors to assess digitalization, waste management, green procurement, and energy-efficient operations. Beside that externally explores ecosystem protection, stakeholder collaboration, and regulatory compliance. The results  showed  that Map Ta Phut port demonstrated the most comprehensive sustainability initiatives within its geo-logistics framework, while Songkhla port and Ranong port showed moderate progress. These variations highlight the differing levels of preparedness and commitment to sustainability across the selected ports. Successful implementation of geo-logistics in this research requires strong governmental support, financial incentives, and capacity building to empower Thai SMPs toward long-term sustainability and enhanced competitiveness in the global maritime sector. Lastly, this framework offers a practical roadmap for transforming regional ports into resilient, green, and smart logistics hubs. ER